1999
DOI: 10.1111/j.1151-2916.1999.tb02228.x
|View full text |Cite
|
Sign up to set email alerts
|

Si NMR Study of the Hydration of Ca3SiO5 and ß‐Ca2SiO4 in the Presence of Silica Fume

Abstract: 29 Si magic-angle spinning nuclear magnetic resonance (MASNMR) was used to study the room-temperature hydration of C 3 S, ␤-C 2 S, and reactive ␤-C 2 S mixed with different amounts of silica fume (SF) that had been hydrated up to nine months and longer. The overall CaO:SiO 2 molar ratios of the mixes were 0.12, 0.20, 0.35, 0.50, and 0.80. NMR spectroscopy was used to quantify the remaining starting materials and the resulting hydration products of different species. A broad peak assigned to Q 3 , appearing in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 24 publications
3
9
0
3
Order By: Relevance
“…These changes are most likely related to the alteration of the silica surface during dissolution. This interpretation is in line with previous studies [31,32] in which it was observed that dissolution of microsilica in alkaline (Ca-dominated) media led to the formation of Q 3 species. These were assigned fully [31] or in large part [32] to the silica; in the latter study, it was shown by 1 H- 29 Si CP MAS NMR that these species can be assigned to a hydrated layer on the surface of the microsilica.…”
Section: Degree Of Reaction (Dissolution Method)supporting
confidence: 82%
See 1 more Smart Citation
“…These changes are most likely related to the alteration of the silica surface during dissolution. This interpretation is in line with previous studies [31,32] in which it was observed that dissolution of microsilica in alkaline (Ca-dominated) media led to the formation of Q 3 species. These were assigned fully [31] or in large part [32] to the silica; in the latter study, it was shown by 1 H- 29 Si CP MAS NMR that these species can be assigned to a hydrated layer on the surface of the microsilica.…”
Section: Degree Of Reaction (Dissolution Method)supporting
confidence: 82%
“…This interpretation is in line with previous studies [31,32] in which it was observed that dissolution of microsilica in alkaline (Ca-dominated) media led to the formation of Q 3 species. These were assigned fully [31] or in large part [32] to the silica; in the latter study, it was shown by 1 H- 29 Si CP MAS NMR that these species can be assigned to a hydrated layer on the surface of the microsilica. Another study [33] found that formation of a significant amount of Q 3 species took place also during dissolution of microsilica in 1 M NaOH solution, but no unequivocal assignment was given.…”
Section: Degree Of Reaction (Dissolution Method)supporting
confidence: 82%
“…These results have been confirmed by Thermogravimetry, Differential Thermal Analysis and Scanning Electric Microscopy. The hydration mechanism proposed confirms previous data of Nuclear Magnetic Resonance of Solids (RMN) of 29 Si of the authors of this paper. …”
supporting
confidence: 91%
“…The evolution of the hydrated phases, formed in the first instants of the reaction, has been studied by laboratory X ray diffraction with a time resolution of 36 min. 29 Si of the authors of this paper.…”
Section: In Situ X-ray Difraction Study Of Hidration Of Caal 2 O 4 -Amentioning
confidence: 92%
See 1 more Smart Citation